Making time : astronomical time measurement in Tokugawa Japan - Frumer, Yulia (Studies of the Weatherhead East Asian Institute, Columbia University., 2018)
What is time made of? We might balk at such a question, and reply that time is not made of anything-it is an abstract and universal phenomenon. In 'Making Time, ' Yulia Frumer upends this assumption, using changes in the conceptualization of time in Japan to show that humans perceive time as constructed and concrete. In the mid-16th century, when the first mechanical clocks arrived in Japan from Europe, the Japanese found them interesting but useless, because they failed to display time in units that changed their length with the seasons, as was customary in Japan at the time. In 1873, however, the Japanese government adopted the Western equal-hour system as well as Western clocks.